2021
DOI: 10.3390/biology10010066
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tristetraprolin in the Resolution of Inflammation

Abstract: Inflammation is a crucial part of immune responses towards invading pathogens or tissue damage. While inflammatory reactions are aimed at removing the triggering stimulus, it is important that these processes are terminated in a coordinate manner to prevent excessive tissue damage due to the highly reactive inflammatory environment. Initiation of inflammatory responses was proposed to be regulated predominantly at a transcriptional level, whereas post-transcriptional modes of regulation appear to be crucial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…As transcriptional changes (DDNS) appeared to explain only parts of the total gene expression changes (DGE) under hypoxia, and since post-transcriptional modes of regulation, including mRNA stability regulation, are known to commonly contribute to gene expression changes in response to extended stimulations [ 21 , 22 ], we next determined differentially stability regulated (DSR) mRNAs under hypoxic conditions. Therefore, we labeled THP-1 cells for 8 h with 4sU, i.e., four pulses of 30 µM 4sU every 2 h during the last 8 h of the experiment to ensure sufficient labeling ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…As transcriptional changes (DDNS) appeared to explain only parts of the total gene expression changes (DGE) under hypoxia, and since post-transcriptional modes of regulation, including mRNA stability regulation, are known to commonly contribute to gene expression changes in response to extended stimulations [ 21 , 22 ], we next determined differentially stability regulated (DSR) mRNAs under hypoxic conditions. Therefore, we labeled THP-1 cells for 8 h with 4sU, i.e., four pulses of 30 µM 4sU every 2 h during the last 8 h of the experiment to ensure sufficient labeling ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The present results showed high levels of serum TTP along with high levels of measured inflammatory cytokines, indicating that TTP could not display a downregulation of these measured inflammatory cytokines in MetS. In this regard, numerous studies have demonstrated that TTP activity is modulated through its phosphorylation, which controls its ability to bind and lead the target ARE-mRNAs for degradation [18,[39][40][41]. To support this, Marchese et al found that TTP phosphorylation through the mitogen-activated protein kinase (MAPK) p38 pathway inhibits the recruitment of the CAF1 deadenylase complex and prevents TTP from degrading ARE-mRNAs [33].…”
Section: Discussionmentioning
confidence: 51%
“…Tristetraprolin (TTP), or zinc-finger protein 36 (ZFP36), is a well-characterized zinc finger-containing RNA-binding protein, acting as a post-transcriptional regulator of immune functions through binding to the adenosine and uridine (AU)-rich elements (AREs) of the mRNAs 3 untranslated regions (3 UTRs), and recruits deadenylase complexes leading to the degradation of its target mRNAs [17,18]. As an mRNA decay activator protein, studies have established that TTP/ZFP36 binds to AREs of several inflammatory factors, like interlukin-6 (IL-6), IL-23 [19], TNF-α [20], IL-10 [21], CXCL1, CXCL2 [22], IL-17 [23], and CCL3 [24], resulting in the degradation of mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…The TTP family includes Zinc finger protein 36 (ZFP36; commonly referred to as TTP), ZFP36-like 1 (ZFP36L1) and ZFP36-like 2 (ZFP36L2) [ 73 ]. These RBPs are characterized by the presence of one or more ZF domain(s) that contain three cysteine residues and one histidine residue [ 74 ]. Mechanistically, they function by binding to the AU-rich elements within the 3′-untranslated regions (UTRs) of their target mRNAs in a sequence- and structure-specific manner through a highly conserved ZF domain and catalyzing the removal of the poly(A) tail, thus resulting in their mRNA decay [ 73 , 74 , 75 ].…”
Section: Rna-binding Proteins (Rbps)mentioning
confidence: 99%